Piecewise Evolutionary Spectra: A Practical Approach to Understanding Projected Changes in Spectral Relationships Between Circulation Modes and Regional Climate Under Global Warming - Putrasahan, D. A.; von Storch, J.‐S.; von Storch, J.‐S.; 1 Max Planck Institute for Meteorology Hamburg Germany (Geophysical Research Letters, 2021)
Regional climate variability is strongly related to large‐scale circulation modes. However, little is known about changes in their spectral characteristics under climate change. Here, we introduce piecewise evolutionary spectra to quantify time‐varying variability and co‐variability of climate variables, and use ensemble periodograms to estimate these spectra. By employing a large ensemble of climate change simulations, we show that changes in the variability and relationships of the North Atlantic Oscillation (NAO) and regional surface temperatures are disparate on individual timescales. The relation between NAO and surface temperature over high‐latitude lands weakens the most on 20‐year timescales compared to shorter timescales, whereas the relation between NAO and temperature over subtropical North Africa strengthens more on shorter timescales than on 20‐year timescales. These projected evolution and timescale‐dependent changes shed new light on the controlling factors of circulation‐induced regional changes. Accounting for them can lead to the improvement of future regional climate predictions. Plain Language Summary: Large‐scale atmospheric circulation modes influence regional climate variability. For example, the North Atlantic Oscillation (NAO) is a circulation mode closely linked to surface temperatures variations over Europe, Africa, and North America. However, under global warming, changes in regional climate variability and their relation to circulation modes (co‐variability) can evolve differently and disparately depending on timescales. Here, we use the theory of evolutionary spectra to quantify these nonstationary changes and present a novel approach to estimate such changes on various timescales. The estimation approach is based on a large ensemble of climate change simulations. We show that changes in the NAO and regional surface temperature variability and their relationships evolve differently on individual timescales. On 20‐year timescales, co‐variability between NAO and surface temperature ...